Wireless communication system power reduction energy consumption - Taher, Montadar Abas; Mandeep Singh Jit Singh; Mardina Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2021)
Most of the multicarrier wireless communication systems such as Worldwide Interoperability for Microwave Access (WiMAX) and Long Term Evaluation (LTE) employ the Orthogonal Frequency Division Multiplexing (OFDM) because of its capability to deliver high data transmission rate through multipath channels. However, OFDM has some limitations due to high Peak to Average Power Ratio (PAPR). PAPR leads to Bit Error Rate (BER) performance degradation. Various PAPR reduction techniques have been proposed such as; Amplitude Clipping (AC), Selected Mapping (SLM), and Constellation Reshaping (CR). Various PAPR reduction techniques have been proposed such as; Amplitude Clipping (AC), Selected Mapping (SLM), and Constellation Reshaping (CR). AC is efficient and simple but has low BER performance; SLM produces high BER performance but needs highly complex computation; CR sometimes degrades the BER performance and needs to send some bits of side information just like the SLM approach to recover the original data. Consequently, there is a trade-off between the computational complexity and the BER performance. The PAPR problem has recognized to be one of the major issues of the multicarrier modulation systems, such as the OFDM systems. The high values of the PAPR derive the system to work in the saturation region of the power amplifier, therefore; out of band radiation and in band distortion will appear. Hence, the OFDM system will suffers from the intermodulation distortion, causing the BER performance to be degraded significantly.